The Influence of Training Programs and Commitment Organization on the Employee Performance of PT Dua Kelinci Pati - Ramadhan Choiri Yuda, Gita; Palupi, Majang (International Journal of Economics, Business and Innovation Research, 2024)
This study determined the influence of training programs and commitment organizations on PT Dua Kelinci Pati employees' performance. The variables used are a training and commitment program organization as independent variables. While variable performance is the dependent variable. The research method used is quantitative and technical data collection using a questionnaire. Data collection techniques sample is non-probability sampling with purposive sampling technique. Number sample as many as 85 respondents. Data was tested using the SPSS 27.0 program, which used descriptive statistical analysis, assumption testing classic, and hypothesis testing. Research results show that the training program and commitment to the organization positively influence the performance of PT Dua Kelinci Pati employees, both simultaneously and partially.